Influencing factors of users’ shift to buying expensive virtual gifts in live streaming: Empirical evidence from China - Cao, Junwei; Zhang, Guihua; Liu, Dong; Shang, Meng (Frontiers in Psychology, 2022)
The market size of live streaming on the Internet, in which the streamer earns profit by prompting users to give virtual gifts through emotional labor, is getting bigger and bigger. However, most users will only buy cheap virtual gifts in live streaming, therefore exploring how to promote users to buy expensive virtual gifts is a valuable topic in live commerce research. Based on social presence theory and information overload theory, this study used the PLS-SEM method to investigate the factors influencing live streaming users to shift from buying cheap virtual gifts to buying expensive virtual gifts, and analyzed the moderating role of information overload in these relationships. The results show that immediate interaction anxiety, verbal intimacy, and virtual physical intimacy positively influence users' shift to purchasing expensive virtual gifts, and that perceived network size and perceived financial risk are negative factors in users' shift to purchasing expensive virtual gifts. Information overload has a moderating role in the relationship between immediate interaction anxiety and switch intention, and it also plays a moderating role in the relationship between perceived network size and perceived financial risk on users' switch intention.